Pengaruh Kepemimpinan Dan Budaya Organisasi Terhadap Motivasi Dan Kinerja Pegawai Pada Dinas Sosial Dan Pemberdayaan Masyarakat Kota Tarakan - Juliansyah, Muhammad Fuad; Kaningsih, Ana Srie; Milwan, Milwan (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2024)
The purpose of this study was to determine and analyze the influence of leadership and organizational culture on the motivation and performance of employees at the Department of Social and Community Empowerment of Tarakan City, either directly or indirectly. This study uses a quantitative method with a "survey" approach to obtain data and information related to research variables at the Department of Social and Community Empowerment of Tarakan City. All employees of the Tarakan City Social and Community Empowerment Service, amounting to 49 people as the population as well as the research sample. The types and sources of data needed in this study are in the form of primary data and secondary data, while to obtain these data by distributing questionnaires and literature studies. To test and prove the hypothesis is done statistically by path analysis (path analysis). Based on the results of research and data analysis found that leadership has a positive and significant effect on employee work motivation, the better the leadership, the more motivating employees' work. Organizational culture has a positive and significant effect on employee work motivation, the better the organizational culture is carried out, the more motivating employees work. Work motivation has a (negative) and insignificant effect on employee performance. Leadership does not have a significant positive effect on employee performance. Organizational culture has a positive and significant effect on employee performance, the better the organizational culture is carried out, the more employee performance will be. There is a simultaneous positive and significant influence of leadership, organizational culture and motivation on employee performance. Motivation does not mediate the influence of leadership and organizational culture on employee performance.